pH-Responsive therapeutic solid lipid nanoparticles for reducing P-glycoprotein-mediated drug efflux of multidrug resistant cancer cells - Chen HH (Dove Medical Press, 2015)
Hsin-Hung Chen,1 Wen-Chia Huang,2 Wen-Hsuan Chiang,2 Te-I Liu,2 Ming-Yin Shen,2,3 Yuan-Hung Hsu,4 Sung-Chyr Lin,1 Hsin-Cheng Chiu2 1Department of Chemical Engineering, National Chung Hsing University, Taichung, 2Department of Biomedical Engineering and Environmental Sciences, National Tsing Hua University, 3Department of Surgery, National Taiwan University Hospital-Hsinchu Branch, 4Pharmaceutical Optimization Technology Division, Biomedical Technology and Device Research Laboratory, Industrial Technology Research Institute, Hsinchu, Taiwan Abstract: In this study, a novel pH-responsive cholesterol-PEG adduct-coated solid lipid nanoparticles (C-PEG-SLNs) carrying doxorubicin (DOX) capable of overcoming multidrug resistance (MDR) breast cancer cells is presented. The DOX-loaded SLNs have a mean hydrodynamic diameter of ~100 nm and a low polydispersity index (under 0.20) with a high drug-loading efficiency ranging from 80.8% to 90.6%. The in vitro drug release profiles show that the DOX-loaded SLNs exhibit a pH-controlled drug release behavior with the maximum and minimum unloading percentages of 63.4% at pH 4.7 and 25.2% at pH 7.4, respectively. The DOX-loaded C-PEG-SLNs displayed a superior ability in inhibiting the proliferation of MCF-7/MDR cells. At a DOX concentration of 80 µM, the cell viabilities treated with C-PEG-SLNs were approximately one-third of the group treated with free DOX. The inhibition activity of C-PEG-SLNs could be attributed to the transport of C-PEG to cell membrane, leading to the change of the composition of the cell membrane and thus the inhibition of permeability glycoprotein activity. This hypothesis is supported by the confocal images showing the accumulation of DOX in the nuclei of cancer cells and the localization of C-PEG on the cell membranes. The results of in vivo study further demonstrated that the DOX delivered by the SLNs accumulates predominantly in tumor via enhanced permeability and retention effect, the enhanced passive tumor accumulation due to the loose intercellular junctions of endothelial cells lining inside blood vessels at tumor site, and the lack of lymphatic drainage. The growth of MCF-7/MDR xenografted tumor on Balb/c nude mice was inhibited to ~400 mm3 in volume as compared with the free DOX treatment group, 1,140 mm3, and the group treated with 1,2 distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy(polyethylene glycol)] solid lipid nanoparticles, 820 mm3. Analysis of the body weight of nude mice and the histology of organs and tumor after the administration of DOX-loaded SLNs show that the SLNs have no observable side effects. These results indicate that the C-PEG-SLN is a promising platform for the delivery of therapeutic agents for MDR cancer chemotherapy. Keywords: pH-responsive, solid lipid nanoparticles, multidrug resistance, permeability glycoprotein